A dual hesitation fuzzy VIKOR method with incomplete attribute weights for property service quality evaluation - Jingjing An; Xingxian Zhang; Lijun Liu; Wenjin Zuo (International Journal of Strategic Property Management)
The evaluation of property service quality is a typical multi-index evaluation problem, which has the characteristics of comprehensiveness and incomplete information in the modern service industry environment. To solve the above problem, we propose a dual hesitation fuzzy VIKOR comprehensive decision method based on incomplete attribute weights for evaluating property service quality. The method integrates innovative distance measurement, comprehensive weighting, and VIKOR decision technology to address challenges such as incomplete information, unknown weights, and evaluator hesitation. By incorporating the information value of dual hesitation fuzzy set hesitancy, we have designed a new distance measurement formula and developed a comprehensive weighting method that combines subjective and objective data. The dual hesitation fuzzy VIKOR model utilizes these tools to calculate utility values and regret values in order to make scientifically grounded decisions. This approach provides robust support for enhancing property service quality and demonstrates broad potential applications in fuzzy information processing and other domains.